Obesity and brain inflammation: a focus on multiple sclerosis. (18th January 2016) - Palavra, F.; Almeida, L.; Ambrósio, A. F.; Reis, F.
Summary: The increase in prevalence of obesity in industrialized societies is an indisputable fact. However, the apparent passive role played by adipocytes, in pathophysiological terms, has been gradually substituted by a metabolically active performance, relevant to many biochemical mechanisms that may contribute to a chronic low‐grade inflammatory status, which increasingly imposes itself as a key feature of obesity. This chronic inflammatory status will have to be integrated into the complex equation of many diseases in which inflammation plays a crucial role. Multiple sclerosis (MS) is a chronic inflammatory condition typically confined to the central nervous system, and many work has been produced to find possible points of contact between the biology of this immune‐mediated disease and obesity. So far, clinical data are not conclusive, but many biochemical features have been recently disclosed. Brain inflammation has been implicated in some of the mechanisms that lead to obesity, which has also been recognized as an important player in inducing some degree of immune dysfunction. In this review, we collected evidence that allows establishing bridges between obesity and MS. After considering epidemiological controversies, we will focus on possible shared mechanisms, as well as on the potential contributions that disease‐modifying drugs may have on this apparent relationship of mutual interference.